2018
DOI: 10.1093/milmed/usx209
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Rates Among Active Duty Service Members Compared with Civilian Counterparts, 2005–2014

Abstract: The objective of this study was to compare military suicide rates with civilian suicide rates, adjusting for age and sex differences that exist between the two populations. The number of active component (AC) service members whose manner of death was certified as suicide was determined for specific age and sex groups for each year from 2005 to 2014. Indirect standardization was then used to determine the expected number of suicides for each age/sex group, based on the U.S. suicide rates for the corresponding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…Given the continued rise in rates of suicide among U.S. military personnel and veterans (Reimann and Mazuchowski, 2018;Department of Veterans Affairs, 2019), understanding the extent to which common mental health diagnoses, such as PTSD, are associated with SI, SA, and suicide is important. Building upon the systematic review by Pompili et al (2013), the current systematic review provides an update of literature spanning 2010-2018, focused on U.S. service members and veterans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the continued rise in rates of suicide among U.S. military personnel and veterans (Reimann and Mazuchowski, 2018;Department of Veterans Affairs, 2019), understanding the extent to which common mental health diagnoses, such as PTSD, are associated with SI, SA, and suicide is important. Building upon the systematic review by Pompili et al (2013), the current systematic review provides an update of literature spanning 2010-2018, focused on U.S. service members and veterans.…”
Section: Discussionmentioning
confidence: 99%
“…Within the United States (U.S.), suicide remains a significant public health concern, with the Centers for Disease Control and Prevention (CDC) recently reporting it as the tenth overall leading cause of death (Heron, 2018). Risk for suicide is especially pronounced among U.S. military personnel and veterans, among whom adjusted suicide rates have, at times, outpaced suicide rates in the general U.S. non-veteran adult population (Reimann and Mazuchowski, 2018;Department of Veterans Affairs, 2019). As such, preventing suicide among military personnel and veterans remains a top clinical priority of the Departments of Defense and VA.…”
Section: Introductionmentioning
confidence: 99%
“…Veterans are one such group: according to a recent report by the Department of Veteran's Affairs (), the suicide rate for Veterans is 1.5 times higher (adjusting for age and sex) than the rate for non‐Veteran adults. And although suicides among active duty military personnel have historically been comparable to or lower than civilian suicide rates (Reimann & Mazuchowski, ), suicide among active duty service members is a growing concern given sharp increases in the suicide rate for this population in recent years (Armed Forces Health Surveillance Center, ; Kuehn, ). Thus, the aim of the present study was to better understand suicidal behavior in the military by examining associations between a potential novel risk factor—interoceptive deficits—and suicidality in a large, military sample.…”
mentioning
confidence: 99%
“…Recently, researchers undertook a comprehensive analysis adjusted for demographic and other differences and found that-contrary to popular belief-rates of military suicide, historically, were actually lower than that of the civilian population. Something did change in 2005-military suicide rates began to increase up to that of the civilian population (Reimann & Mazuchowski, 2018). However, it does not appear the increase in suicide rates was due to combat exposure or the stress of deployments as was commonly assumed; in fact, rates for the never-deployed active duty, Reserve and Guard components also increased.…”
Section: Mental Health Conditions (Mhcs) In 2008 Rand Released the mentioning
confidence: 97%